2017
DOI: 10.1111/conl.12412
|View full text |Cite
|
Sign up to set email alerts
|

Call for a Paradigm Shift in the Genetic Management of Fragmented Populations

Abstract: Thousands of small populations are at increased risk of extinction because genetics and evolutionary biology are not well-integrated into conservation planning-a major lost opportunity for effective actions. We propose that if the risk of outbreeding depression is low, the default should be to evaluate restoration of gene flow to small inbred populations of diploid outbreeding organisms that were isolated by human activities within the last 500 years, rather than inaction. We outline the elements of a scientif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
363
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 355 publications
(374 citation statements)
references
References 29 publications
9
363
0
2
Order By: Relevance
“…According to population genetic theory, if inbreeding is present in a population, statistical associations will form between molecular markers and the genome (Hansson & Westerberg, ), thereby enabling the use of molecular markers to estimate GWH (see Introduction; Szulkin et al, ). Thus, using the g2 statistic to quantitatively evaluate an arguably crucial aspect of GWH, namely inbreeding (Ralls et al, ), is a valuable approach for examining the informativeness of alternative marker sets. Further, examining the expected correlations between marker heterozygosity and population inbreeding (using equations 3 and 4 from Miller et al, ) lends greater confidence to assessments of how closely our marker sets reflect GWH.…”
Section: Discussionmentioning
confidence: 99%
“…According to population genetic theory, if inbreeding is present in a population, statistical associations will form between molecular markers and the genome (Hansson & Westerberg, ), thereby enabling the use of molecular markers to estimate GWH (see Introduction; Szulkin et al, ). Thus, using the g2 statistic to quantitatively evaluate an arguably crucial aspect of GWH, namely inbreeding (Ralls et al, ), is a valuable approach for examining the informativeness of alternative marker sets. Further, examining the expected correlations between marker heterozygosity and population inbreeding (using equations 3 and 4 from Miller et al, ) lends greater confidence to assessments of how closely our marker sets reflect GWH.…”
Section: Discussionmentioning
confidence: 99%
“…It has also recently been shown that the addition of foreigners does not lead to as high rates of erosion of local adaptation as originally thought (i.e., decreased rate of sweeps; Tigano & Friesen, 2016). Hence, the risks associated with outbreeding depression and foreign advantage may dissipate rapidly (Aitken & Whitlock, 2013;Harrisson et al, 2016;Ralls et al, 2017;Roitman et al, 2017;Tigano & Friesen, 2016). Hence, the risks associated with outbreeding depression and foreign advantage may dissipate rapidly (Aitken & Whitlock, 2013;Harrisson et al, 2016;Ralls et al, 2017;Roitman et al, 2017;Tigano & Friesen, 2016).…”
Section: Risks and Trade-offs Associated With Assisted Gene Flowmentioning
confidence: 95%
“…Characterizing and conserving genomic variation within species is a key challenge in conservation genetics (Frankham, Ballou, & Briscoe, ; Ralls et al, ). The decreasing cost and ease with which genome‐scale data can now be produced has allowed the generation of extensive population genomic data sets that can be used to monitor and manage populations (Allendorf, Hohenlohe, & Luikart, ; Morin, Luikart, & Wayne, ).…”
Section: Introductionmentioning
confidence: 99%